2019
DOI: 10.1016/j.ijproman.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A configurational explanation for performance management systems' design in project-based organizations

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Egwunatum [5], found in their studies, that the relationship between various independent variables and project success varies according to the project life cycle. [6], found in his research, that CSFs do not give real life knowledge of a project's success.…”
Section: A Project Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Egwunatum [5], found in their studies, that the relationship between various independent variables and project success varies according to the project life cycle. [6], found in his research, that CSFs do not give real life knowledge of a project's success.…”
Section: A Project Performancementioning
confidence: 99%
“…Rooij et al, [6] argued that project management team members' technical background is crucial for the success of projects. However, [8], found in their research, that a project management team is not fully responsible for the success or failure of their project.…”
Section: Organizational Culture-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that project planners and designers are important for project success. [6], found in their studies, that lack of communication between parties in a project is a significant factor affecting project performance in Iraq.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[11], found in their studies that, the critical sources of delay in Iraq government related construction projects are insufficient contractor's working capital and poor site management practices of the contractor. [6] stated that delay by subcontractors is one of the causes for delay in construction projects in Egypt.…”
mentioning
confidence: 99%